Evaluasi Satuan Pendidikan Aman Bencana (SPAB) di Satuan Pendidikan Dasar Wilayah Pesisir Selatan Bantul (Kalurahan Parangtritis, Kapanewon Kretek, Kabupaten Bantul) - Agus Triyono; Purbudi Wahyuni; Eko Teguh Paripurno; Arif Rianto Budi Nugroho; Puji Lestari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The Disaster Safe Education Unit Program is a national policy aimed at building school community preparedness in facing potential disasters through three main components: safe school facilities, disaster management in schools, and disaster risk reduction education. The southern coastal area of Bantul, particularly Parangtritis Village, has a high level of vulnerability to threats such as earthquakes, tsunamis, and coastal abrasion, making the implementation of Disaster Safe Education Unit Program in this region highly crucial. This study aims to evaluate the implementation of the Disaster Safe Education Unit Program in elementary education units located in the coastal area of Parangtritis using the CIPP evaluation model (Context, Input, Process, Product). This research employs a qualitative descriptive approach, with data collected through in-depth interviews, field observations, and a review of Disaster Safe Education Unit Program documents. The research informants include school principals, teachers, students, members of the Parangtritis Disaster-Resilient Village, and representatives from the Regional Disaster Management Agency and the Department of Education, Youth, and Sports. Data analysis was conducted through data reduction, data presentation, and conclusion drawing based on the four dimensions of the CIPP model. The findings indicate that, in the context aspect, there is awareness of the importance of SPAB, but it is not yet supported by strong internal policies. In the input aspect, human resources and facilities remain limited. The process aspect shows that disaster drills and training activities are still incidental and have not been disseminated to all members of the school community. Meanwhile, in the product aspect, there has been an increase in students’ basic preparedness knowledge, but it has not yet resulted in comprehensive disaster-resilient behavioral change. In conclusion, the implementation of Disaster Safe Education Unit Program in elementary schools in the Parangtritis Village area is categorized as adequate, but requires strengthening of school policies, enhancement of teacher capacity, and cross-sector collaboration among schools, government agencies, and the community to realize safe and resilient schools. Keywords: Disaster Safe Education Unit, program evaluation, CIPP model, disaster preparedness, southern coastal Bantul.